(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Asthma is a chronic inflammatory disease of the small airways that affects all age groups. Asthma symptoms lead to impairment in the physical, emotional and social aspects of patient’s life. Bronchial asthma can be correlated to Swasakasam as per siddha text book Yugi vaithiya chinthamani 800. In Swasakasam patients, respiratory symptoms are important determinants of reduced health related quality of life. Evaluation of Health Related Quality of Life (HRQoL) is a primary outcome measure in patient with chronic disease. The objective of the study is to assess the HRQoL in Swasakasam patients and to evaluate the risk factors associated with it. It was a hospital based observational study of which 100 asthma patients were evaluated to quality of life who were reporting at OPD of Ayothidoss Pandithar Hospital, National Institute of Siddha (NIS) through Asthma Quality of Life Questionnaire (AQLQ). In this study, asthma affects females more than males (63% and 32%) and with 2% of male children. For the total patient population, there was a maximum limitation in physical activity domain (2.22±0.41) of HRQoL compared to other 3 domains. In case of sub score of all domains the mean of emotional function domain is lesser in female patients than male. Bronchial asthma significantly affects QOL. To reduce the asthma severity yoga, Pranayamam may be used adjunctively with standard medication in bronchial asthma patients and awareness should be given to improve their quality of life and to reduce the number of asthma attacks per week.